Potensi Alga Merah dan Alga Hijau untuk Menghambat Pertumbuhan Bakteri Eschericia coli - KETUT SRIE MARHAENI JULYASIH; NI PUTU RISTIATI; IDA BAGUS PUTU ARNYANA (Fakultas Pertanian Universitas Udayana, 2020)
Potential of Red Algae and Green Algae to Inhibit Escherichia coli Bacteria Growth. The use of synthetic chemicals as a control for the growth of E. coli bacteria that causes of diarrhea children can cause adverse effects on health, so it needs natural control ingredients that do not cause impacts on human health. One natural controller to inhibit bacterial growth is by utilizing natural sources, including seaweed. The purpose of this study was to examine the potential of seaweed as an anti-bacterial agent of E. coli. The research used seaweed extract of Eucheuma spinosum, Euchuema cottonii, Gracilaria spp., and Caulerpa spp. The test parameters observed were the inhibition zone (mm) of each seaweed extract treatment using a ruler and measured the inhibition zone distance. The results showed that E.cottonii seaweed extract had the highest inhibitory ability with an inhibition zone diameter of 11.1 mm, including the moderately sensitive category, then Caulerpa spp. with a inhibition zone diameter of 10.0 mm, Gracilaria spp has the ability to inhibit E.coli bacteria with a inhibition zone diameter of 6.9 mm, including the insensitive category, and the lowest in seaweed E. spinosum with a inhibition zone diameter of 4.2 mm. including the insensitive category.